Direct and indirect effects of R&D cooperation on the innovation of Italian firms - Otello Ardovino; Luca Pennacchio; Giuseppe Piroli (Economics and Econometrics Research Institute (EERI), 2014)
Firm innovation capacity depends not only on internal capabilities, but also on external expertise and knowledge acquired through cooperation. This paper analyzes direct and indirect effect of R&D cooperation on the innovation of Italian firms. Using a multivariate probit model to account for the complementarity of four different types of innovation activity and the heterogeneity in the choice of cooperation partners, we find strong and positive direct effects of collaborations with some non-competitive partners (suppliers, clients, private research institutes and consultants). Also R&D cooperation with competitors shows a relevant direct effect on firm innovation. On the contrary, collaborations with university have weaker effects; this could perhaps be due to the short-term perspective adopted in the study. These findings suggest that it is important to look at the specific type of R&D collaborations because they have a different impact on the success of innovative activities. On the other hand, indirect effects are scant and restricted to cooperation with some non-competitive partners. Such a result suggests that absorptive capacity of firms and R&D spillovers are quite weak in Italian context. Lastly, firm size and sector-specific features also affect innovation propensity.
Keywords: L13; O30; O32; 330; R&D collaboration; absorptive capacity; moderating variable; innovation; equation probit model; community innovation survey